Forest and Land Fire Analysis Based Hotspot and Burned Area in Pelalawan District, Riau Province - Ati Dwi Nurhayati; Wanda Aulia (Jurnal Silvikultur Tropika, 2022)
Riau Province always occurs forest and land fires every year. One of the districts that are often burned is Pelalawant. Pelalawan District has the highest number of hotspots in the 2015-2019 period. This study aims to analyze the distribution of hotspots and burned areas in 2015 and 2019 in Pelalawan District Riau. Data used in this study comes from the MODIS Terra/Aqua satellite imagery. The results showed that the number of hotspots in Pelalawan Regency was 2168 in 2015 and 1503 in 2019. In 2015 the number of hotspots was dominated on non-peat land and in 2019 dominated on peatland. Pangkalan Kuras District had the highest number of hotspots in 2015 and Teluk Meranti District had the highest number of hotspots in 2019. The area burned in 2015 was 50,896,207 ha in Pelalawan Regency and 8,078,358 ha in 2019. Keywords: burned area, forest and land fire, hotspot, Pelalawan District